Performance Evaluation of Turnover Intentions of Employees’ Productive Behavior and Supply Chain Strategy (Studies in Islamic Microfinance Institutions) - Anna Widiastuti; Mutamimah Mutamimah; A. Khoirul Anam; Aida Nahar (International Journal of Supply Chain Management, 2020)
Abstract- This study discusses the occurrence of turnover intentions that are influenced by productive behavior of employees and moderated by the supply chain strategy of Islamic microfinance institutions, namely Baitul Mal Wat Tamwil (BMT). What distinguishes it from previous studies is that the quality culture is attempted to moderate the influence of employee’s productive behavior on turnover intentions. In addition, this study also analyzes separately between the dimensions that exist in employee’s productive behavior variables as independent variables that affect turnover intentions. By using 100 samples determined by the Census (Saturated Sampling) method, the research was analyzed quantitatively, whilst the data was processed by using Partial Least Square (SMART-PLS Software) application. The finding of the study failed to prove that the productive behavior, supply chain strategy, and the culture quality of the employees are the moderating variables affecting the turnover intentions, except one dimension of the work stress which had a significant effect on them.